Use of A3-method by engineering students in industry projects. Issue 6 (24th April 2021) - Oversluizen, Gerlinde; Slomp, Jannes
Abstract: The A3 problem-solving method, developed at Toyota, is taught in many different educational programmes and used in industry and service organizations. Although the interest in the A3-method is growing, there is little systematic research on the way it supports users in problem solving and communication. In this paper, a study is presented on the appreciation of the A3-method as it is used in industry assignments performed by higher education students. A survey was performed, with closed and open questions, to gain the experience of 133 senior bachelor students. The study shows that students, especially appreciate the structure offered by the A3-method. The concise A3-format is, furthermore, helpful in the communication with stakeholders. The study also identifies the difficulties students experience while executing the elements in the A3-method. Several of these difficulties are related to the industrial context of the problem. A lot of companies lack a structure and culture in which continuous improvement is thoroughly embedded.